A highly robust heterometallic TbIII/NiII–organic framework for C2 hydrocarbon separation and capture. Issue 13 (22nd January 2020) - Chen, Hongtai; Zhuang, Gui-Lin; Fan, Liming; Zhang, Xiutang; Gao, Lin-Na; Sun, Di
Abstract : The exquisite combination of hetreometallic [Tb III Ni II (COO)3 (H2 O)] clusters with a designed hexatopic ligand generates one highly robust three-dimensional heterometallic Tb III /Ni II –organic framework material. Abstract : The exquisite combination of hetreometallic [Tb III Ni II (COO)3 (H2 O)] clusters with a designed hexatopic ligand generates one highly robust three-dimensional heterometallic Tb III /Ni II –organic framework material {[TbNi(HTDP)(H2 O)]·3DMF·2H2 O} n (NUC-2 ; H6 TDP = 2, 4, 6-tri(2, 4-dicarboxyphenyl)pyridine). Gas adsorption measurements reveal that the activated NUC-2 exhibits ultrahigh C2 H2 adsorption capacity but negligible uptake of C2 H4, which is ascribed to its high stability and ultrahigh functional internal surface. Furthermore, dynamic breakthrough experiments confirm that NUC-2 can effectively fulfill the separation of a C2 H2 /C2 H4 (1 : 99) mixture. Such excellent performance makes NUC-2 a promising adsorbent for practical C2 H2 /C2 H4 separation and provides new insights into heterometallic MOFs for gas separation.